Banking Governance According to the principles of the Basel Committee and its impact on the achievement of the strategic objectives of banks Study in a sample of private commercial banks Iraqi - محمد, محمد جاسم (Journal of Economics and Administrative Sciences, 2014)
This study aims to impact statement played by banking governance according to the decisions of the Basel Committee in achieving the strategic objectives of the banks, But order to achieve the this goal has been the adoption of two hypotheses in addition to the two main hypotheses as sub answered preliminary The study seeks to verify their health and two (no correlation relationship and impact between Banking  governance and achieve strategic objectives), has been tested hypotheses. Study has reached multiple of the most important conclusions: - 1 - There a correlation relationship between Banking governance and achieve strategic objectives. 2 -There is a impact relationship between banking governance and achieve strategic objectives.The study included a number of recommendations, most notably the following: - 1 - Work encourage by the principles of Banking  governance as one important component of the financial safety to achieve strategic objectives of the banks. 2 Taking into account the importance of the relationship between the banking and Banking Governance standards to achieve strategic objectives, in the evaluation of performance deviations from what is planned and the subject within strategic objectives.